Philippines Students’ Perception (ESL) of Indonesian Professional Teacher (EFL) - Fatimah, Eva; Husain, Ahmad; Sunmud, Sakina (Cakrawala: Jurnal Pendidikan, 2022)
This study examines professional teachers in student perception of EFL teachers and ESL Students. Professional teacher become the next level of teacher labelled. Teachers will be categorized as professional if they master several domains such as teacher knowledge and understanding, teacher practice, and teacher relation. This research is a descriptive qualitative with 20 students of the Transfer Credit Program of Tarlac Agricultural University as the population and 13 students as a sample with a random sampling technique. Data collection of this research through questionnaires and interviews to collect the data and analyse with descriptive analysis and Nvivo as a tool to analyze and visualize the data. This research revealed ESL Student's perceptions stated many negative facts such as language barrier that constructed among them, online learning limited their thought to achieve in their class, and also a duplicate question on their exam seems like a question on the internet. ESL Students also revealed many positive facts such as management class and given a same opportunities to speak in class, innovative teaching method, teaching structured well, and teacher deliver a great material to achieve the objective of the subject matter